(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
Morphologic and morphometric data of a lion-like cat skull found in the Zandobbio (Lombardy -Italy) Eemian ossiferous rubble and stored in the Civic Museum of Natural History "E. Caffi" of Bergamo are presented. The skull shows the typical lion morphology and its relatively small dimensions suggest that it belonged to a female individual. Carnassial tooth analysis underlines advanced lion characters already recognized in Italy during the Eemian. According to skull and teeth characters it is possible to ascribe the specimen to the group of Upper Pleistocene lion-like cats Panthera leo spelaea (Goldfuss, 1810). The presence of P. leo spelaea in the Quaternary deposit of Zandobbio has remarkable importance not only locally. In fact, besides being the first report of this great feline at Zandobbio, it is the second report from Lombardy and, the oldest certain P. leo spelaea finding and the oldest complete P. leo spelaea skull known from Italy to date. The advanced P. leo spelaea characters were already present in Italy during the Eemian. SHORT NOTE